Success Factors of Malaysian eBay Entrepreneurs: Skills, Attitudes and Strategies for Digital Growth - Yaacob, Roslinda (Journal of Techno-Social, 2025)
The focus is on digital entrepreneurship in Malaysia with specific reference to eBay site, the purpose of the study being to precise the skills, attitudes and strategies that enhance the success of those involved in the business. Even though the Malaysian DKN 2030 (full) and MyDIGITAL projects recognize digital entrepreneurship as a hope for the country’s economy growth, only some of the eBay entrepreneurs in Malaysia may be recognized as ‘Top Rated Sellers’. This research uses qualitative research technique and conducts a series of semi-structured interviews with 10 Malaysian eBay successes. The research evidence suggests that ability to manage stock control, integrated tools in the internet and social networks like SEO (full), and the employees’ favorable personality attributes like perseverance and lobbying. Also, proper use of e-marketing techniques and strong brand image are some of the critical success factors that yielded demonstrated positive outcomes. The result of this research opens the way into theory, practice, and policy, it does open pathways where entrepreneurs require adequate programs and training programs for getting better results. As for the suggestions for the future studies, they include the investigation of social networks, the impact of AI and blockchain on them, as well as the quantitative methods to enhance the understanding of this subject.